Comparative clinical evaluation of efficacy and safety of a formulation containing ciclopirox 8% in the form of a therapeutic nail lacquer in two different posologies for the treatment of onychomycosis of the toes Avaliação clínica comparativa da eficácia e da segurança de formulação contendo ciclopirox a 8% na forma de esmalte terapêutico em duas diferentes posologias no tratamento de onicomicoses dos pododáctilos - Sergio Schalka; Samanta Nunes; Antonio Gomes Neto (Anais Brasileiros de Dermatologia, 2012)
BACKGROUND: The use of topical antifungal agents in the treatment of onychomycosis is of great value in clinical practice as there are different limitations regarding the use of systemic treatment. OBJECTIVE: To evaluate the efficacy and safety of a nail lacquer formulation containing ciclopirox 8% in two different posologies: the traditional regimen (3/2/1) and a regimen of weekly use. METHODS: A blind, randomized, comparative trial which included 41 patients divided into 02 groups, with Group I using the nail lacquer once weekly and Group II using the traditional regimen (3/2/1). Both groups applied the medication for 06 months. RESULTS: The species most frequently found in groups I and II were Trichophyton rubrum (55% and 61.9%) and Trichophyton mentagrophytes (30% and 19%). There was a tendency to a higher level of treatment resistance by T. mentagrophytes infection in both groups, without any predilection for sex, age, proportion of the nail affected at the beginning of the study, duration of the clinical disease and quantity of nails affected per person. Both groups had significant levels of mycological cure, clinical response and therapeutic success and there was no statistically significant difference between groups I and II (p >0.05). CONCLUSION: The nail lacquer containing ciclopirox 8% was equally effective at a weekly dose when compared to the traditional dosing (3/2/1), allowing a more comfortable regimen. FUNDAMENTOS: A utilização de antifúngicos tópicos na terapêutica da onicomicose é de grande valor na prática clínica, visto que há diferentes limitações ao uso das opções terapêuticas sistêmicas. OBJETIVO: Avaliar comparativamente a eficácia e a segurança de uma formulação de esmalte de ciclopirox a 8% em dois diferentes esquemas posológicos: o esquema tradicional (3/2/1) e um esquema posológico de uso semanal. MÉTODOS: Foi realizado um estudo cego, comparativo e randomizado que incluiu 41 pacientes, divididos em dois grupos, sendo o grupo I submetido ao esquema posológico de uma vez por semana e o grupo II submetido ao esquema posológico tradicional (3/2/1). Os grupos utilizaram a medicação por 180 dias. RESULTADOS: As espécies mais frequentemente encontradas nos grupos I e II foram Trichophyton rubrum (55% e 61,9%) e Trichophyton mentagrophytes (30% e 19%). Houve tendência de maior resistência ao tratamento pelo T. mentagrophytes nos dois grupos estudados, sem predileção por sexo, idade, proporção de acometimento ungueal inicial, tempo de evolução do quadro ou número de unhas acometidas por indivíduo. Ambas as modalidades apresentaram índices significativos de cura micológica, resposta clínica e sucesso terapêutico, e não houve diferença estatisticamente significante entre os grupos I e II (p > 0,05). CONCLUSÃO: O esmalte contendo ciclopirox a 8% mostrou-se igualmente eficaz na posologia de uma vez por semana quando comparada à posologia tradicional (3/2/1), permitindo um esquema posológico mais confortável.